Dimensions of Hotel Service Quality in Mongolia - Badarch, Lkhamtseden; Zanabar, Altanchimeg (Jurnal Ilmiah Peuradeun, 2017)
Service quality has emerged as an important area in the hotel industry for decades. Thus, it is essential that service providers understand customer expectations and perceptions as well as the factors that influence their evaluation and satisfaction with the provided service. Hotel industry is growing each year in Mongolia. Realizing the increase in competition among hotels, hotel managers are focusing on improving the elements which contribute to service quality for customers of the hotel industry in Mongolia. The quality of service in hotel industry is an important factor of successful business. This study identifies the effects of various elements of hotel industry which affects customer satisfaction. Almost all researchers utilized service quality model and adopted their SERVQUAL instrument, based on the concept that service quality differs from industry to industry. Examining additional dimensions, identified by customers, it should be included in the service quality concept. Further, the level of importance of each specific dimension for the users of hotel services in Mongolia is then measured.